Study Abroad: A Path to Lifetime Learning - He, Xiaohong; Jackson, Anita L.; Lodha, Shyam S. (University Of Connecticut Center for International Business Education and Research, 2004)
Keywords: Foreign countries; Foreign study; American students; dept.mkt; faculty_collection

Co-branding partners: What do they see in each other? - Prince, M.; Davies, M. (Business Horizons, 2002)
The decision about whether to co-brand is based on two conditions: the opportunities for creating a competitive advantage, and the operational benefits that will result. When these conditions are favorable, a firm must pick the right co-branding partner, using such criteria as (a) compatibility between brands, (b) market volatility, (c) investment requirements and arrangements, and (d) the prospective partner's commitment to the agreement. The firm and its chosen partner then enter the phase of courtship and potential conflict, which involves planning, negotiation, and conflict avoidance and management. Finally, they must create an exit strategy, in case the co-branding arrangement fails to live up to its promise.
Keywords: dept.mkt; peer-reviewed

Diamond geezers - Prince, M. (Business Strategy Review, 2005)
Keywords: dept.mkt

Inside Advertiser and Agency Relationships: A Hands-On Guide for Practitioners - Prince, Melvin; Davies, Mark (Lulu. com, 2006)
Keywords: dept.mkt

The joint effect of Relevant/Irrelevant information and expertise on the formation of market segments: do experts group in fewer, tighter clusters? - Stevens, Laurie A; Spence, Mark T (Australian and New Zealand Marketing Academy Conference, 2005)
Keywords: dept.mkt; ⛔ No DOI found

Dynamics of trust between clients and their advertising agencies: advances in performance theory - Davies, Mark; Prince, Melvin (Academy of Marketing Science Review, 2005)
Keywords: dept.mkt; ⛔ No DOI found

Marketing mix standardization: a cross cultural study of four countries - Kustin, Richard Alan (International Business Review, 2004)
The study researched the possibility of standardizing the marketing mix by investigating the cross-cultural responses from the United States, Brazil, France and India. The study tested the premise of standardization by determining if respondents perceived specific attributes of a common non-durable consumer product the same or differently. The results indicate the opportunity for dynamic marketing standardization remains limited but applicable within specific cultural country markets. Several attribute perceptions between US and foreign respondents are found to be more similar than dissimilar suggesting advantages may exist for a limited implementation of marketing mix standardization as part of a global marketing strategy. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Consumer product; Cross-culture; Globalization; Hofstede; International marketing; Marketing mix; Standardization; dept.mkt

The animal within - Prince, Melvin; Davies, Mark (Business Strategy Review, 2004)
Keywords: dept.mkt

Consumer Income and Beliefs Affecting Happiness - Prince, Mel; Manolis, Chris (Advances in Quality-of-Life Theory and Research, 2003)
Recent syntheses of empirical studies have clearly demonstrated a consistently positive relationship between income and happiness. Research is needed to reduce uncertainty and disentangle such relationships, which have been found to be quite modest, but significant in the aggregate. The present study contributes to this end, in that it investigates the moderating effect of income on the relationship between beliefs that serve as internal buffers and happiness. We go beyond simple associations of income and happiness to examine relationships between income and self-esteem and between income and optimism. Finally, causal modeling is employed to demonstrate that, under varying income levels, these beliefs affect happiness by the same process — with distinct yet predictable outcomes.
Keywords: beliefs; causal model; dept.mkt; happiness; income; money

A model of job performance, job satisfaction, and life satisfaction among sales and sales support employees at a pharmaceutical company - Prince, Melvin; Engle, Robert L; Laird, Kenneth R (Journal of Pharmaceutical Marketing & Management, 2003)
This study investigates the influence of role conflict, role ambiguity, and role strain on job performance, job satisfaction, and life satisfaction among field sales and company sales support employees in a single pharmaceutical company. Because this study is based on data from a single company, these results may not necessarily be generalized to all companies in the industry. In the present research, a path model of the process reveals important variations in response to role conflict, role ambiguity, and role strain between the two classes of employees. For both classes, the influence of decreased role ambiguity is generally positive for measured outcomes. However, reductions in role conflict, while lessening role strain, are likely to result in lower job performance for field sales employees. Decreases in role strain, while improving life satisfaction, may lead to lower job satisfaction for sales support employees. © 2003, Informa UK Ltd All rights reserved: reproduction in whole or part not permitted. All rights reserved.
Keywords: Job performance; dept.mkt; job satisfaction; life satisfaction; pharmaceutical sales; role strain

Factors affecting encoding, retrieval, and alignment of sensory attributes in a Memory‐Based brand choice task - Shapiro, Stewart; Spence, Mark T. (Journal of Consumer Research, 2002)
Sensory attributes, such as sound quality ascertained by listening to a stereo, are often ambiguous and therefore difficult to encode and retrieve. Despite this, consumers often place more weight on these attributes compared to verbally described market information when making brand choice decisions. Results from two studies demonstrate that providing criteria to evaluate the sound quality of competing brands of stereos facilitates the encoding, retrieval, and alignment of the sensory attribute in a brand choice task. Study 1 shows that without criteria to evaluate sound quality during trial, memory for this attribute is poor. Further, perceptions of sound quality assimilate to conflicting market information, which adversely affects decision performance. The reverse is true when evaluative criteria and a scheme to rate the criteria are provided: memory for sound quality improves, perceptions of sound quality contrast with conflicting market information, more weight is placed on sound quality when decision making, and better choices are made. Study 2 shows that providing evaluative criteria during product trial enhances performance through improvement in the encoding process.
Keywords: dept.mkt; peer-reviewed

Moderator teams: an extension to focus group methodology - Prince, Mel; Davies, Mark (Qualitative Market Research: An International Journal, 2001)
Traditional focus group methodology involves an individual trained moderator who manages the whole process from writing the focus group guide that directs the topics pursued, the interaction with participants, to interpretation, reporting and client feedback. Since their training, personality and orientation can vary differentially, this may lead to moderator bias. Proposes a new method that involves a series of complementary moderators that target specific areas of the guide that allows them to specialise in their particular experiences and orientations. These moderators are used sequentially on the same groups that offer the potential to avoid many of the problems associated with single-moderator discussion groups. Moreover, the chance to moderate the moderator keeps a check on how the sessions of each focus group develops, building in feedback between moderators, and reduces the prospects of misinterpretation and side-tracking by a single moderator. © 2001, MCB UP Limited
Keywords: Equal value; Focus groups; Management; dept.mkt

The entry of international CPA firms into emerging markets: motivational factors and growth strategies - Kirsch, Robert J; Laird, Kenneth R; Evans, Thomas G (The International Journal of Accounting, 2000)
This article examines the entry of professional service firms, specifically the Big Six international accounting firms, into emerging foreign markets and explores how they develop and expand their business once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. A conceptual model is employed to illustrate the interrelationship between a firm's specific characteristics, the foreign environment, and foreign subsidiary intrafirm structure. Growth potential, client needs, favorable political/legal climate, and cultural considerations emerged as important factors in determining market entry and growth strategies for professional services firms. The research findings broaden our understanding of factors that influence professional services firms' development of pricing and marketing mix strategies. While all firms surveyed offered a full range of services, their marketing mix strategy differed from domestic approaches because of various local constraints on pricing and promotion. Copyright © 2000 University of Illinois.
Keywords: Commonwealth of independent States; Eastern European and Baltic States; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt

A marketing resource-based model of international market entry and expansion for professional services firms - Laird, Kenneth R; Kirsch, Robert J; Evans, Thomas G (Services Marketing Quarterly, 2003)
This paper examines the entry of the Big Six international accounting firms, into emerging foreign markets and explores marketing resource considerations once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. The paper presents a marketing resource-based model based upon relevant research. The model focuses on firm specific resource capabilities interacting with the foreign business environment and the foreign intrafirm structure as a determinant of foreign market entry choice and eventual market expansion. The research findings broaden our understanding of factors that influence professional services firms' development of marketing resource strategies when expanding globally. While all firms surveyed offered a full range of services, their marketing resource strategy differed from domestic approaches because of various local constraints on marketing mix elements. © 2003 Taylor & Francis Group, LLC.
Keywords: Commonwealth of Independent States; Eastern European and Baltic states; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt

A latent class analysis of brand prestige - Prince, Melvin; Davies, Mark (Model Assisted Statistics and Applications, 2009)
Core constructs are necessary as a basis for scale development in brand prestige research. This study examines the theoretical rationale for two such concepts - brand excellence and status conferral - and uses latent class scaling in an empirical test as to whether they are both important independent dimensions of prestige brands. Based on the analysis, these concepts are shown to be consistently present for two brands in two diverse product categories. The research calls into question earlier work on the measurement of brand prestige that was premised on a one-dimensional concept of prestige. Further studies are needed to explore the dimensionality and substantive structure of the brand prestige concept, to confirm or disconfirm findings from this research. © 2009 IOS Press. All rights reserved.
Keywords: Brand excellence; Latent class scaling; Prestige brand; Status conferral; dept.mkt

Qualitative analysis and the construction of causal models - Prince, Melvin; Manolis, Chris; Tratner, Susan (Qualitative Market Research: An International Journal, 2009)
Purpose: The purpose of this paper is to provide a methodology by which qualitative analyses serve as rich source materials for discovery of theoretically cogent interrelations between latent variables. Design/methodology/approach: In an illustrative case, qualitative data are collected from US franchisee managers from a single branded franchise of automotive repair outlets. Qualitative analysis of franchisee experiences and attitudes is critical for construction of a causal model used to predict conflict intensity between franchisee managers and franchisors. Findings: The model is based on franchisees' normative expectations for resource allocation within the franchise; and their perceptions of franchisor normative violations, which are determinative of grievances, distrust, and hostility. This theoretical orientation serves to generate a system of interrelated empirically testable propositions. Research limitations/implications: In principle, the primary limitation of using qualitative analysis for the construction of causal models is the fruitfulness of the theoretical orientation shared by the qualitative analyst and the causal modeler. Practical implications: The methodological approach advanced in this paper advances qualitative research and causal modeling beyond the individual contributions. Qualitative analysis infuses variables and process imagery into causal modeling. In turn, causal modeling elaborates the qualitative analysis and makes explicit logical connections between variables. Originality/value: This paper advances a methodology by which qualitative analysis and causal model construction may be usefully integrated. Theory-based qualitative analysis may be formalized to map latent concepts and their interrelations. Further, operational measures of these concepts may be adduced from the analysis of textual data. © Emerald Group Publishing Limited.
Keywords: Modelling; Qualitative methods; dept.mkt

A study of hofstede's culture value survey in a post-soviet country - Kustin, Richard Alan (Journal of Transnational Management, 2006)
This research examines the four culture dimensions developed by Hofstede's 1980 and 1983 studies exploring the potential of management-employee conflict. In the present study, employee responses to Hofstede's national culture survey were performed in Belarus, formerly of the Soviet Union, in order to establish a culture score for each of Hofstede's four culture dimensions in a centrally planned economy. The results of the research run counter to some of the stereotypic cultural characteristic expectations, and support others of the cultural values attributable to the Republic of Belarus, an autocratic political and economic state in Eastern Europe. Copyright © by The Haworth Press, Inc. All rights reserved.
Keywords: Belarus; Cross culture; Cultural survey; Culture dimensions; Eastern Europe; Eurasia; Europe; Hofstede; International management; culture; dept.mkt; geographical research; survey